2021
DOI: 10.5114/ait.2021.103735
|View full text |Cite
|
Sign up to set email alerts
|

The association between intraoperative cell salvage and red blood cell transfusion in cardiac surgery – an observational study in a patient blood management centre

Abstract: Cardiac surgery is commonly associated with high blood loss and the need for allogeneic red blood cell (RBC) transfusion. In addition, 20-30% of cardiac surgical patients suffer from anaemia [1]. Brouwers et al. [2] analysed > 11,000 cardiac surgical patients and revealed a transfusion rate of > 50%. Karkouti et al. [3] analysed > 9000 patients undergoing cardiac surgery and revealed that severe intraoperative blood loss is associated with an 8.1-fold higher mortality rate. Studies indicate that allogeneic RBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Although the use of red cell salvage is incorporated in PBM programmes, the cost effectiveness of cell salvage and the reduction of adverse outcomes by reducing allogeneic RBC transfusion requirements is still under debate. However, many studies suggest that cell salvage is associated with a decreased proportion of patients exposed to allogeneic RBC transfusions as an individual measure in a comprehensive PBM programme 409–414 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the use of red cell salvage is incorporated in PBM programmes, the cost effectiveness of cell salvage and the reduction of adverse outcomes by reducing allogeneic RBC transfusion requirements is still under debate. However, many studies suggest that cell salvage is associated with a decreased proportion of patients exposed to allogeneic RBC transfusions as an individual measure in a comprehensive PBM programme 409–414 …”
Section: Discussionmentioning
confidence: 99%
“…However, many studies suggest that cell salvage is associated with a decreased proportion of patients exposed to allogeneic RBC transfusions as an individual measure in a comprehensive PBM programme. [409][410][411][412][413][414] Although autologous platelet-rich plasmapheresis has been proposed as a blood conservation technique in complex cardiovascular surgery, whether it can improve clinical outcomes remains unclear. [415][416][417] The indications for autologous platelet-rich plasmapheresis require further study, particularly whether it is beneficial to lowrisk patients.…”
Section: Cell Salvagementioning
confidence: 99%
“…19 On the contrary, Neef et al found that cell salvage was significantly associated with a reduced number of allogeneic RBC transfusions. 20 Only 40% of patients included in our analysis required blood or blood product transfusion (Figure 2). There was no significant difference in blood transfusion requirements between the cell saver group and the no cell saver group.…”
Section: Discussionmentioning
confidence: 99%
“…Blood sample collections should be reduced to the absolute necessary numbers, blood sample collection tubes should draw as little blood volume as possible, and return systems for blood sample collections should be established. Washed cell salvage—the collection, washing and retransfusion of a patient’s own wound blood—can help to reduce the need for blood from other sources [ 21 , 26 ].…”
Section: Discussionmentioning
confidence: 99%